The relationship between soldierâs body readiness level and the anxiousness tendency of students in the flyer academy of the Indonesian Air Force Army Adisutjipto Airbase Yogyakarta - Sumarni DW, Wahyudi Cecep Sugeng Kristanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
Training the Indonesian Air Force flyers takes a lot of time and fund. The cramped trainingschedule, demand of discipline and achievement, and intense stress from the fear of dying fromplane accidents give the flyer students an even bigger stress that could potentially lead toanxiousness. In the selection of flyer candidates in the field, the most important aspect to benoticed is the body readiness of the candidates, whereas the mental health is frequently leftunchecked. There was a case in a training session where a flyer student experienced a badmental and academic achievement that, after being traced, resulted from poor mental healthtest, although the military body readiness test was good. It left the country with a loss fromhaving to discharge the student. The aim of this study was to identify the relationship betweenthe military body readiness level and the anxiousness tendency of a flyer apprentice. This was anobservational study with cross-sectional design. The research subjects was the flyer students ofthe Indonesian National Air Force Army in Adisutjipto Airbase Yogyakarta. The sample was takenfrom all of the subjects which fulfilled the inclusion and exclusion criteria. The measurement ofthe anxiousness used the TMAS (Taylor Manifest Anxiety Scale), whereas the military bodyreadiness value was taken directly in the field test. Moreover, psychological stress was alsomeasured using Instrument of Psychosocial Stressor Assessment (IPSP). The results were analyzedusing Chi-Square test and multiple regression analysis. It was found that there was no significantlyrelationship between the military body readiness value and the anxiousness tendency of theflyer student in the flyer academy of the Indonesian National Air Force Army in AdisutjiptoAirbase Yogyakarta (p>0,05). The psychological stress factor has a role in creating the anxiousnesstendency of the flyer students.